Excitation of vibrationally-excited ultralong-range strontium Rydberg molecules in quantum gases. Issue 12 (January 2020) - Ding, R; Whalen, J D; Kanungo, S K; Killian, T C; Dunning, F B; Yoshida, S; Burgdörfer, J
Synopsis: The photoexcitation rate for ultralong-range Rydberg molecules is sensitive to the initial spatial sepa-ration of the atoms from which they are formed. Here we explore the photoexcitation of different molecular vibrational states as a probe of spatial correlations in a cold atomic gas.